FUSION INDUCED BY ENERGY-INTENSIVE MULTIFUNCTION CAVITATION IN CONJUNCTION WITH POSITRON IRRADIATION - Yoshimura, Toshihiko (International Journal of Engineering Science Technologies, 2023)
This review summarizes the development of multifunction cavitation technology and assesses future applications for this process. The focus is on attempts to increase the surface strength and functionality of various metals and plastics and to elucidate the conditions that can induce nuclear fusion by cavitation. An experimental setup capable of producing cavitation fusion based on positron-irradiated laser-assisted high-field energy-intensive functional cavitation is described, having the same basic structure as a prior device without positron irradiation. A combination of water jet, ultrasonic and magnetic field energy sources has been found to increase the sonoluminescence intensity and to theoretically exceed the threshold required for the D-T fusion reaction. This paper describes the incorporation of positron and laser energy sources to this system as a means of further increasing the internal temperature and pressure values of bubbles. Specifically, a Na-22 positron beam source was placed in the upper part of the reaction vessel in the direction of the magnetic field such that positrons were imparted to cavitation bubbles floating on the surface of degassed heavy acetone. These positrons were partially annihilated by interactions with electrons via the Compton effect to generate gamma-rays and energy via the reaction e+ + e- → 2γ + l.02 MeV. This energy promoted the D-T chain reaction D + T → 4He + n + 14 MeV to increase the probability of cavitation fusion.